2022
DOI: 10.15585/mmwr.mm715152a1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Clinical Features of Mpox in Transgender and Gender-Diverse Adults — United States, May–November 2022

Abstract: As of November 9, 2022, a total of 28,730 cases of monkeypox (mpox) had been reported in the United States,* primarily among adult cisgender men reporting recent male-to-male sexual contact (1). Transgender and gender-diverse persons, who constitute an estimated 0.5% of the U.S. adult population, † face unique health disparities and barriers to care (2-4). However, data on the epidemiologic and clinical features of Monkeypox virus infections in this population are limited (5). CDC analyzed U.S. case surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Monkeypox (mpox) cases in the 2022 outbreak have primarily occurred among adult gay, bisexual, and other men who have sex with men (MSM); however, other populations have also been affected ( 1 ). To date, data on mpox in cisgender women and pregnant persons have been limited.…”
mentioning
confidence: 99%
“…Monkeypox (mpox) cases in the 2022 outbreak have primarily occurred among adult gay, bisexual, and other men who have sex with men (MSM); however, other populations have also been affected ( 1 ). To date, data on mpox in cisgender women and pregnant persons have been limited.…”
mentioning
confidence: 99%
“…Similarly, a participant who marked no change to a behavior is not necessarily an indication that the behavior occurred or occurred within a time frame that would be relevant for potential mpox exposure risk. In addition, the small numbers of transgender persons in this analysis do not allow us to examine their reports of sexual behavior change separately, despite evidence that transgender persons nationally have accounted for a disproportionate share of mpox virus infections 13 . Despite these limitations, our findings could be extended to understand how individuals who engage in behaviors associated with mpox transmission use prevention messages, whether in lieu of or in addition to vaccination; this information is pivotal to the development of interventions to increase vaccine uptake and vaccine coverage.…”
Section: Discussionmentioning
confidence: 99%
“…While disaggregated reporting of sexual orientation and gender identity are among the best practices for data collection, we combined gender identity, sexual orientation (for men), and gender identity of sex partners to reflect categories that were inclusive of gender identity and to distinguish groups at higher risk for mpox virus infection, including MSM. Transgender persons have experienced a disproportionate prevalence of mpox virus infections, 13 but the number of transgender women (n = 5) and transgender men (n = 3) in this analysis were too small to analyze their reports of behavior change separately. Men, including transgender men, were categorized as MSM if they reported sex with men or transgender men in the past 14 days or they reported their sexual orientation as gay or bisexual.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, among the more than 90 000 cumulative monkeypox cases globally, approximately 98% occurred in areas where no previous epidemics had been documented 1,4,5 . As one of the nonendemic countries most severely affected by the monkeypox epidemic, the United States has reported over 30 000 confirmed cases, with a majority of them reported in adult males who have sex with other males 6 . These findings indicated that the monkeypox outbreak had spread extensively worldwide, particularly in nonendemic countries that may lack adequate experience in prevention and control.…”
Section: Introductionmentioning
confidence: 99%